2005
DOI: 10.1111/j.1600-0420.2005.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine receptors in human corneal epithelium and endothelium

Abstract: ABSTRACT.Purpose: Monoamine receptors are found throughout the body. Reports about the presence of monoamine receptors in the human cornea are inconsistent. Methods: Immunohistochemistry, immunofluorescence and immunoblotting were used to localize monoamine receptor sites on human corneal epithelium and endothelium. Results: Antibodies to alpha-1, beta-1 and beta-2 adrenergic receptors and to D1-like and 5HT-7 receptors were bound in corneal epithelium. Antibodies to alpha-1, alpha-2A, beta-1 and beta-2 adrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 16 publications
0
27
0
5
Order By: Relevance
“…However, the increase in CCT was statistically significant one month after initiation of tamsulosin treatment. The presence of α-1 receptors in freshly fixed human corneal epithelium and endothelium was demonstrated by Grueb et al 18 Moreover, direct radioligand binding studies indicate that intact corneal epithelial and endothelial cells exhibit α-1 adrenergic receptors. 19 Alpha-1 adrenergic receptors seem to be associated with regulation of inositol-1,4,5-tris-phospate formation.…”
mentioning
confidence: 80%
“…However, the increase in CCT was statistically significant one month after initiation of tamsulosin treatment. The presence of α-1 receptors in freshly fixed human corneal epithelium and endothelium was demonstrated by Grueb et al 18 Moreover, direct radioligand binding studies indicate that intact corneal epithelial and endothelial cells exhibit α-1 adrenergic receptors. 19 Alpha-1 adrenergic receptors seem to be associated with regulation of inositol-1,4,5-tris-phospate formation.…”
mentioning
confidence: 80%
“…Although there was functional evidence for the presence of ␣ 2 -adrenergic receptors in corneal epithelial cells [12] , the ␣ 2 -receptor subtype had not been demonstrated in corneal epithelium for a long time. Recent studies have shown the presence ␣ 2A -adrenergic receptors in freshly fixed human corneal endothelium [14] . Our examination of bovine corneal epithelial and endothelial cells confirmed the presence of ␤ 1 -and ␤ 2 -adrenergic receptors in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ␤ -adrenergic receptors on corneal epithelial and endothelial cells has been established [8,9,14] . Corneal epithelial ␤ -adrenergic receptors have been associated with stimulation of adenylyl cyclase and cAMP-dependent protein kinase, as well as chloride secretion [13,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Additionally, direct radioligand binding studies indicate that intact corneal epithelial and endothelial cells both exhibit α1 adrenergic receptors. 16 Alpha-1 adrenergic receptors seem to play a role in regulation of inositol-1,4,5-tris-phospate formation. 17 Although the physiological role of α1 adrenergic receptors and their second messengers phosphatidyl inositol and cyclic AMP in corneal epithelium and endothelium is not clear, they may be involved in the regulation of corneal homeostasis and fluid transportation.…”
Section: Discussionmentioning
confidence: 99%